Multi-modal exercise training and protein-pacing enhances physical performance adaptations independent of growth hormone and BDNF but may be dependent on IGF-1 in exercise-trained men. (February 2017) - Ives, Stephen J.; Norton, Chelsea; Miller, Vincent; Minicucci, Olivia; Robinson, Jake; O'Brien, Gabe; Escudero, Daniela; Paul, Maia; Sheridan, Caitlin; Curran, Kathryn; Rose, Kayla; Robinson, Nathaniel; et al.
Abstract: Objective: Protein-pacing (P; 5–6 meals/day @ 2.0 g/kg BW/day) and multi-mode exercise (RISE; resistance, interval, stretching, endurance) training (PRISE) improves muscular endurance, strength, power and arterial health in exercise-trained women. The current study extends these findings by examining PRISE on fitness, growth hormone (GH), insulin-like growth factor-1 (IGF-1), and brain-derived neurotrophic factor (BDNF) response, cardiometabolic health, and body composition in exercise-trained men. Design: Twenty active males (> 4 days exercise/week) completed either: PRISE (n = 11) or RISE (5–6 meals/day @ 1.0 g/kg BW/day; n = 9) for 12 weeks. Muscular strength (1-repetition maximum bench and leg press, 1-RM BP, and 1-RM LP), endurance (sit-ups, SU; push-ups, PU), power (squat jump, SJ, and bench throw, BT), flexibility (sit-and-reach, SR), aerobic performance (5 km cycling time-trial, TT), GH, IGF-1, BDNF, augmentation index, (AIx), and body composition, were assessed at weeks 0 (pre) and 13 (post). Results: At baseline, no differences existed between groups except for GH (RISE, 230 ± 13 vs. PRISE, 382 ± 59 pg/ml, p < 0.05). The exercise intervention improved 1-RM, SJ, BT, PU, SU, SR, 5 km-TT, GH, AIx, BP, and body composition in both groups (time, p < 0.05). However, PRISE elicited greater improvements in 1-RM BP (21 vs. 10 ∆ lbs), SJ (171 vs. 13 ∆ W), 5 km-TT (− 37 vs. − 11 ∆ s), and sit-and-reach (5.3 vs. 1.2 ∆ cm) over RISE alone (p < 0.05) including increased IGF-1 (12%, p < 0.05). Conclusions: Exercise-trained men consuming a P diet combined with multi-component exercise training (PRISE) enhance muscular power, strength, aerobic performance, and flexibility which are not likely related to GH or BDNF but possibly to IGF-1 response. Graphical abstract: Highlights: Multi-modal training that incorporates resistance, interval, stretch, and endurance exercise training components (RISE), improves multiple aspects of fitness (muscle strength, power, endurance, flexibility, aerobic power), as well as improving cardiometabolic health (cholesterol profile, body composition, blood pressure, vascular stiffness) in previously active normal weight men. When multimodal training is combined with protein-pacing (2.0 g/kg BW/day) greater improvements in fitness related outcomes are realized. The adaptations to the exercise or combined intervention (diet and exercise) do not appear to be related to circulating levels of GH or BDNF but may be due to IGF-1 response.